Maternal care in rural China: a case study from Anhui province - Li Xiaohong; Viisainen Kirsi; Wu Zhuochun; Hemminki Elina (BMC, 2008)
Abstract Background Studies on prenatal care in China have focused on the timing and frequency of prenatal care and relatively little information can be found on how maternal care has been organized and funded or on the actual content of the visits, especially in the less developed rural areas. This study explored maternal care in a rural county from Anhui province in terms of care organization, provision and utilization. Methods A total of 699 mothers of infants under one year of age were interviewed with structured questionnaires; the county health bureau officials and managers of township hospitals (n = 10) and county level hospitals (n = 2) were interviewed; the process of the maternal care services was observed by the researchers. In addition, statistics from the local government were used. Results The county level hospitals were well staffed and equipped and served as a referral centre for women with a high-risk pregnancy. Township hospitals had, on average, 1.7 midwives serving an average population of 15,000 people. Only 10-20% of the current costs in county level hospitals and township hospitals were funded by the local government, and women paid for delivery care. There was no systematic organized prenatal care and referrals were not mandatory. About half of the women had their first prenatal visit before the 13th gestational week, 36% had fewer than 5 prenatal visits, and about 9% had no prenatal visits. A major reason for not having prenatal care visits was that women considered it unnecessary. Most women (87%) gave birth in public health facilities, and the rest in a private clinic or at home. A total of 8% of births were delivered by caesarean section. Very few women had any postnatal visits. About half of the women received the recommended number of prenatal blood pressure and haemoglobin measurements. Conclusion Delivery care was better provided than both prenatal and postnatal care in the study area. Reliance on user fees gave the hospitals an incentive to put more emphasis on revenue generating activities such as delivery care instead of prenatal and postnatal care.